CSIG-08. ABT-414 RESISTANT GBM TUMORS HARBOR THE TEK S466I MUTATION AND EXHIBIT INCREASED STEMNESS. (12th November 2021) - Blomquist, Mylan; Noviello, Teresa; D'Angelo, Fulvio; Sereduk, Christopher; Rabichow, Benjamin; Miller, Aunay; Marin, Bianca-Maria; White, Forest; Sarkaria, Jann; Lasorella, Anna; Iavarone, Antonio; Ceccarelli, Michele; et al.
Abstract: Glioblastoma (GBM), the most common primary brain tumor in adults, remains uniformly fatal due to the lack of effective targeted therapies for this aggressive malignancy. Genomic amplification of epidermal growth factor receptor (EGFR) occurs in 40-60% of primary GBM. Half of all EGFR-amplified cases of GBM also harbor EGFRvIII, a constitutively active, truncated variant of EGFR. The incidence of EGFR alterations in GBM makes inhibition of EGFR/EGFRvIII an attractive therapeutic approach. Depatuxizumab mafodotin (ABT-414) is an antibody-drug conjugate comprised of ABT-806, a mAB against EGFR, and a cytotoxic payload (monomethyl auristatin F). ABT-414 therapy initially showed promising results as an EGFRvIII therapy in vivo and in vitro; however, ABT414 failed to provide a survival benefit in phase I/II clinical trials, potentially due to therapeutic resistance. In this study, we seek to investigate the mechanisms of resistance to ABT-414 by performing whole exome, transcriptome and single cell RNA seq on ABT-414 resistant GBM PDX tumors. Our data showed an enrichment of mutations unique to the ABT-414 resistant tumors, including a point mutation (S466I) in TEK/TIE2 transmembrane angiopoietin receptor. In vitro expression of TEK S466I in GBM cells showed an increase in activation of ERK and STAT3 and increased TEK/TIE2 immunoprecipitation with EGFR compared to the wild-type TEK receptor. Furthermore, gene ontology analysis reveals that ABT-414-treated flank tumors exhibit increased activation of extracellular matrix organization and CNS developmental processes compared to flank tumors in the control treatment groups. ABT-414-treated tumors also demonstrate increased expression of inhibitor of differentiation (ID)1 and ID3, associated with stem-like phenotype in glioblastoma. Taken together, our data indicate that resistance to ABT-414 is mediated by both de novo mutations not detected in the parent tumor and adaptive dysregulation of pathways which may lead to dedifferentiation and therapeutic resistance.